2017
DOI: 10.1038/ncomms15527
|View full text |Cite
|
Sign up to set email alerts
|

Drug-seeking motivation level in male rats determines offspring susceptibility or resistance to cocaine-seeking behaviour

Abstract: Liability to develop drug addiction is heritable, but the precise contribution of non-Mendelian factors is not well understood. Here we separate male rats into addiction-like and non-addiction-like groups, based on their incentive motivation to seek cocaine. We find that the high incentive responding of the F0 generation could be transmitted to F1 and F2 generations. Moreover, the inheritance of high incentive response to cocaine is contingent on high motivation, as it is elicited by voluntary cocaine administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 52 publications
3
84
0
Order By: Relevance
“…This report adds to a growing body of evidence that paternal cocaine exposure produces altered cocaine reward processing and cocaine addiction‐related behavior in first‐generation offspring. Two recent publications indicate that the male offspring of sires exposed to an extensive cocaine self‐administration regimen have altered cocaine self‐administration (Le et al., ; Vassoler et al., ). The current results are consistent with these studies, showing that male, but not female offspring of cocaine‐taking sires have blunted cocaine sensitization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This report adds to a growing body of evidence that paternal cocaine exposure produces altered cocaine reward processing and cocaine addiction‐related behavior in first‐generation offspring. Two recent publications indicate that the male offspring of sires exposed to an extensive cocaine self‐administration regimen have altered cocaine self‐administration (Le et al., ; Vassoler et al., ). The current results are consistent with these studies, showing that male, but not female offspring of cocaine‐taking sires have blunted cocaine sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have consistently shown that sire exposure to cocaine influences cocaine‐associated behaviors in the next generation. For example, the progeny of sires that self‐administered or received non‐contingent cocaine displayed reduced cocaine self‐administration in male offspring (Le et al., ; Vassoler et al., ). Blunted cocaine‐conditioned reward in female offspring of sires that received non‐contingent cocaine also has been observed (Fischer, Rice, Martinez Rivera, Donohoe, & Rajadhyaksha, ).…”
Section: Introductionmentioning
confidence: 99%
“…Following separation into “Addict” F0 and “Non‐addict” F0 rats, they were bred with naïve females to generate F1 and F2 offspring. The “Addict” F1 and F2 offspring displayed increased cocaine self‐administration, while no effect on cocaine self‐administration was detected in the “Non‐addict” F1 and F2 offspring (Le et al ., ). Previous studies that have separated mouse drug‐response into high and low responders have identified numerous genetic differences between these sub‐populations (Radcliffe et al ., ; He et al ., ; Belknap et al ., ).…”
Section: Cocainementioning
confidence: 97%
“…In a study by Le et al . (), Sprague Dawley rats were trained to self‐administer cocaine and then separated into “Addict” F0 rats (top 25% of responders) and “Non‐addict” F0 rats (bottom 40% of responders). Following separation into “Addict” F0 and “Non‐addict” F0 rats, they were bred with naïve females to generate F1 and F2 offspring.…”
Section: Cocainementioning
confidence: 99%
See 1 more Smart Citation